Exogenous emulsifiers and multi-enzyme combination improves growth performance of the young broiler chickens fed low energy diets containing vegetable oil - Samiru Sudharaka Wickramasuriya; Shemil Priyan Macelline; Eunjoo Kim; Taeg Kyun Shin; Hyun Min Cho; Dinesh D. Jayasena; Jung Min Heo (Animal Bioscience, 2022)
Objective The present study examined the effects of exogenous emulsifiers and multi-enzyme supplementation into a low energy density diet on growth performance, visceral organ parameters, blood metabolites, ileal morphology, and nutrient digestibility in broiler chickens from hatch to 21 days. Methods One hundred and sixty-eight one-day-old Ross 308 broiler chickens were allocated in a completely randomized design to 24 pens and each pen was assigned to one of four dietary treatments to give six replications with seven chickens in a cage. Dietary treatments were: i) positive control with standard energy level (PC); ii) negative control with 100 kcal/kg lower energy of the standard level (NC); iii) NC diet supplemented 0.05% calcium stearoyl-2 lactylate as an emulsifier (NC+E); and iv) NC diet supplemented with both 0.05% calcium stearoyl-2 lactylate and 0.05% multi-enzyme (NC+E+M). Corn and soybean meal-based control diets containing vegetable oil were formulated to meet the Ross 308 nutrition specification. Chickens were fed ad-libitum with the treatment diets and sampling was conducted on day 21. Results Our results revealed that emulsifier and multi-enzyme supplementation into NC diets improved (p<0.05) feed efficiency of the broiler chickens compared to the broiler chickens fed NC diets from hatch to 21 days. Supplementation of emulsifier and multi-enzyme into NC diet improved (p<0.05) nutrient digestibility of the broiler chickens. However, emulsifier and multi-enzymesupplementation into diet did not influence (p>0.05) visceral organ weight, blood metabolites, and intestinal morphology in broiler chickens fed NC diets. Conclusion Supplementation of emulsifier and multi-enzyme in the NC diet would support improving growth performance in young broiler chickens with improved feed efficiency and increased nutrient digestibility thereby curtailing the negative impact of energy reduction in the diets.